Expression of cell cycle‐regulated genes and prostate cancer prognosis in a population‐based cohort. Issue 13 (18th May 2015) - Rubicz, Rohina; Zhao, Shanshan; April, Craig; Wright, Jonathan L.; Kolb, Suzanne; Coleman, Ilsa; Lin, Daniel W.; Nelson, Peter S.; Ostrander, Elaine A.; Feng, Ziding; Fan, Jian‐Bing; Stanford, Janet L.
<x xml:space="preserve">Abstract</x> BACKGROUND Prostate cancer (PCa) is clinically and biologically heterogeneous, making it difficult to predict at detection whether it will take an indolent or aggressive disease course. Cell cycle‐regulated genes may be more highly expressed in actively dividing cells, with transcript levels reflecting tumor growth rate. Here, we evaluated expression of cell cycle genes in relation to PCa outcomes in a population‐based cohort. METHODS Gene expression data were generated from tumor tissues obtained at radical prostatectomy for 383 population‐based patients (12.3‐years average follow‐up). The overall mean and individual transcript levels of 30 selected cell cycle genes was compared between patients with no evidence of recurrence (73%) and those who recurred (27%) or died (7%) from PCa. RESULTS The multivariate adjusted hazard ratio (HR) for a change from the 25th to 75th percentile of mean gene expression level (range 8.02–10.05) was 1.25 (95%CI 0.96–1.63; P = 0.10) for PCa recurrence risk, and did not vary substantially by Gleason score, TMPRSS2‐ERG fusion status, or family history of PCa. For lethal PCa, the HR for a change (25th to 75th percentile) in mean gene expression level was 2.04 (95%CI 1.26–3.31; P = 0.004), adjusted for clinicopathological variables. The ROC curve for mean gene expression level alone (AUC = 0.740) did not perform as well as clinicopathological variables alone (AUC = 0.803) for predicting lethal PCa, and the addition of mean gene expression to clinicopathological variables did not substantially improve prediction (AUC = 0.827; P = 0.18). Higher TK1 expression was strongly associated with both recurrent (P = 6.7 × 10−5) and lethal (P = 6.4 × 10−6) PCa. CONCLUSIONS Mean expression level for 30 selected cell cycle‐regulated genes was unrelated to recurrence risk, but was associated with a twofold increase in risk of lethal PCa. However, gene expression had less discriminatory accuracy than clinical variables alone for predicting lethal events. Transcript levels for several genes in the panel were significantly overexpressed in lethal versus non‐recurrent PCa. Prostate 75:1354–1362, 2015. © 2015 Wiley Periodicals, Inc.